Incorporation of air into a snack food reduces energy intake - Osterholt, Kathrin M.; Roe, Liane S.; Rolls, Barbara J. (Appetite, 2007)
This study investigated how the air content of a familiar snack food affected energy intake and whether varying the method of serving the snack modified intake. We tested two versions of an extruded snack (cheese puffs) that were equal in energy density (5.7 kcal/g), but differed in energy per volume (less-aerated snack: 1.00 kcal/ml; more-aerated snack: 0.45 kcal/ml). In a within-subjects design, 16 women and 12 men consumed the snacks ad libitum in the laboratory during four afternoon sessions. A standard volume (1250 ml) of each snack was served once in a bowl and once in an opaque bag. Results showed significant differences in intake of the two snacks by energy ( p=0.0003) and volume ( p<0.0001); subjects consumed 21% less weight and energy (70±17 kcal) of the more-aerated snack than the less-aerated snack, although they consumed a 73% greater volume of the more-aerated snack (239±24 ml). These findings suggest that subjects responded to both the weight and volume of the snack. Despite differences in intake, hunger and fullness ratings did not differ across conditions. The serving method did not significantly affect intake. Results from this study indicate that incorporating air into food provides a strategy to reduce energy intake from energy-dense snacks.